If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3=-x/5
We move all terms to the left:
-3-(-x/5)=0
We get rid of parentheses
x/5-3=0
We multiply all the terms by the denominator
x-3*5=0
We add all the numbers together, and all the variables
x-15=0
We move all terms containing x to the left, all other terms to the right
x=15
| 144-x=99 | | 2y=6+(14+y) | | -126=-3(7-5m) | | 3(1-+p)=-5(p+1 | | -7+7x=-126 | | 9^(x+3)=9^(3x-17) | | 5=-5p-10 | | 9+5x=x-23 | | (10x+5)=(6x-1)=180 | | 4m+5=-5 | | 4(x+32)+4(x+32)=16 | | -4x-2(2x+10)=109 | | 2⋅(x−7)=−20 | | 3(w-2)-2=7 | | 4x+0.4=1.6 | | 6x+28=76-2x | | x+2.9=3.9 | | 4x+19=100−5x | | 9=5w+5 | | 2x+10=34-4x | | 7x=17-10x | | 3(x-1)+5=32 | | 2y=6+14+y | | -3v-33=3(v+7) | | 4x^2-0x+16=0 | | 2w+.4=1+1.8w | | 4b^2-2=182 | | 4(x-7)=0.3(x+2)+11 | | 7y^2-70y+168=0 | | (4x+5)+(3x6)=4x+(5+3x)+6 | | 8t+11=35= | | 5k+2.9=3.9= |